Development of Google Sites Learning Media to Improve Learning Outcomes of Class III Elementary School - Hartari, Rika Oktavia; Putra, Galih Mahardika Christian (JTP - Jurnal Teknologi Pendidikan, 2025)
This study aims to develop web-based google sites learning media in improving student learning outcomes in the content of Natural and Social Sciences (IPAS). This research uses research and development (RnD) method with ADDIE model. This model consists of five steps, namely (1) analyze, (2) design, (3) development, (4) implementation, (5) evaluation. The tools of this research are validation sheets, student test results sheets, data collected through various methods and analysis using validity and reliability tests of material and media experts. The results of the study indicate that Google Sites-based learning media is highly feasible in terms of content and presentation, and effective in improving student learning outcomes. A significant increase in student learning outcomes was observed after the implementation of this media, with the N-Gain test results categorizing the improvement as moderate. The average pre-test score was 62.37, while the post-test score was 85.05, reflecting an increase of 22.68 points. This research can serve as a foundation for developing more complex and interactive learning media.